Sosok dan Peran Ayah dalam Persepsi Anak Yatim - Syibli, Yasin Muhammad (Journal of Islamic Education Counseling, 2021)
This study aims to reveal the perceptions of orphans in Cirebon towards the figureand role of the father, both as a typical / symbolic father and as an individual /personal father. The subjects in this study were 9 students of an elementary school inCirebon, consisting of 5 grade 5 children and 4 grade 6 children (aged 10-12 years)who come from single mother families. Information was collected using the centerbunch dialog / focus group discussion method. Information analysis was carried outusing qualitative content analysis (AIK) methods, using a deductive approach, namelydirected content analysis. In this study, it was found that orphans still have perceptionsabout their personal father, even though they do not live with the father. Theperception of the father's figure tends to be negative, while the perception of thefather's role tends to be positive